2011
DOI: 10.1074/jbc.m111.223172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a New Family of Widely Distributed Metal-independent α-Mannosidases Provides Unique Insight into the Processing of N-Linked Glycans

Abstract: The modification of N-glycans by ␣-mannosidases is a process that is relevant to a large number of biologically important processes, including infection by microbial pathogens and colonization by microbial symbionts. At present, the described mannosidases specific for ␣1,6-mannose linkages are very limited in number. Through structural and functional analysis of two sequence-related enzymes, one from Streptococcus pneumoniae (SpGH125) and one from Clostridium perfringens (CpGH125), a new glycoside hydrolase fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 42 publications
2
78
0
Order By: Relevance
“…The plasmid expressing nixF (predicted to code for an endo-␤-N-acetylglucosaminidase, GH18) did not complement the activity of the ⌬nixE-nixL strain on pNP-␤-GlcNAc, consistent with the endo-activity predicted for this enzyme (data not shown). Similarly and as reported for enzymes belonging to the GH125 family (19), the plasmid expressing nixJ (predicted to code for an ␣-1,6-mannosidase, GH125) was not active on pNP-␣-Man (data not shown). Activity on pNP-Fuc was 11-fold lower when NixE was expressed from pC-nixE as compared with expression from pC-nixE-nixL ( Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The plasmid expressing nixF (predicted to code for an endo-␤-N-acetylglucosaminidase, GH18) did not complement the activity of the ⌬nixE-nixL strain on pNP-␤-GlcNAc, consistent with the endo-activity predicted for this enzyme (data not shown). Similarly and as reported for enzymes belonging to the GH125 family (19), the plasmid expressing nixJ (predicted to code for an ␣-1,6-mannosidase, GH125) was not active on pNP-␣-Man (data not shown). Activity on pNP-Fuc was 11-fold lower when NixE was expressed from pC-nixE as compared with expression from pC-nixE-nixL ( Fig.…”
Section: Resultsmentioning
confidence: 80%
“…More recently, enzymes from Streptococcus pyogenes and Streptococcus pneumoniae classified in the GH38 (␣-1,3-mannosidase) and GH125 (␣-1,6-mannosidase) families, respectively, have been identified. These enzymes are active on N-glycans, highlighting the processing of N-glycans by Streptococcus bacteria (18,19). Finally, it was shown that the human pathogen Capnocytophaga canimorsus deglycosylates surface glycoproteins from the host and supports its growth on the released glycan moiety (20).…”
mentioning
confidence: 99%
“…SPy1604 is an -mannosidase belonging to GH38; it shows specificity for -1,3-and -1,6-mannosyl linkages (Suits et al, 2010), which are frequently associated with N-glycans. SPy1603 shows 62% identity (BLAST; http:// blast.ncbi.nlm.nih.gov) to a GH125 -mannosidase from S. pneumoniae (SpGH125; Gregg et al, 2011). The SpGH125 protein shows exo--1,6-mannosidase activity, which is again consistent with specificity for N-linked glycans.…”
Section: Gene Organizationmentioning
confidence: 81%
“…In retaining GH38 (32), and inverting GH47 (33) GH92 (31) α-mannosidases, a divalent metal ion (Zn 2þ for GH38, Ca 2þ for GH47 and GH92) is found to coordinate the 2-and 3-hydroxyls, possibly assisting in catalysis through substrate distortion and in delivery of the nucleophile (31). By contrast, in the inverting GH125 enzymes no metal ion is observed in any structures and no substrate distortion was seen in a pseudo-Michaelis complex with an S-linked disaccharide spanning the active site (34). It is unclear how this family overcomes the destabilizing diaxial interaction of the attacking water nucleophile, although it is possible that a favorable hydrogen bond between the 2-OH of the sugar and the nucleophilic water may assist in nucleophilic attack in a similar way to the divalent metals in the GH38, GH47, and GH92 enzymes.…”
Section: Discussionmentioning
confidence: 99%